Environmental Management Accounting Practices In Hospital Waste Management: A Legitimacy Theory Perspective - Fitermen, Andi Rezky Fitriana; Mintarti, Sri; Khairin, Fibriyani Nur (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze the implementation of environmental management accounting in waste management at the Inche Abdoel Moeis Regional General Hospital in Samarinda City. Environmental pollution, particularly hospital waste classified as hazardous and toxic (B3), requires an integrated management system that includes an accounting approach to identify, measure, and report environmental costs. This research adopts a qualitative descriptive method with data collected through interviews, observation, and documentation. The findings reveal that the hospital applies environmental management accounting using the PPOPET approach (Planning, Budgeting, Implementation, Operation, Evaluation, and Follow-Up). However, several challenges remain, such as limited detail in environmental cost allocation and weak internal reporting systems. The hospital’s participation in the PROPER program and achievement of a blue rating reflect minimum compliance with environmental standards and a step toward environmental legitimacy. The implementation of environmental management accounting serves as a strategic initiative to enhance decision-making, cost efficiency, and institutional environmental sustainability.